Sexual Health Interventions for Black Women in the United States: A Systematic Review of Literature. Issue 2 (3rd April 2019) - Ware, Samuella; Thorpe, Shemeka; Tanner, Amanda E.
Abstract: Objective: The purpose of this systematic review was to identify and evaluate approaches used in sexual health interventions targeting Black women in the United States. Methods: We conducted a review of 15 sexual health intervention studies for Black women published between January 2000 and May 2017 in the United States. Results: Each intervention focused on HIV/sexually transmitted infection prevention, incorporated an asset and deficit-based approach, primarily used individual-level assets, and was effective in achieving the stated sexual health-related outcomes. Conclusions: Comprehensive sexual health interventions require further development and refinement to include more community and institutional-level assets to improve long-term sustainable change and empower Black women.